Analysis of the effect of work from home on employee performance with the intervening variable of work motivation at the office of the Ministry of Religion, Purbalingga Regency - Rofita Baroroh; Ida Hayu Dwimawanti; Sri Indarti (Jurnal Mantik, 2023)
This study aims to analyze the effect of Work From Home on employee performance with the Intervening variable of Work Motivation. The instrument used is a questionnaire to measure the responses of 53 respondents using the saturated sampling method so that all employees of the Office of the Ministry of Religion of Purbalingga Regency are the population. Data collection was carried out for one week, namely April 2023. The independent variables in this study consisted of Work From Home (X), employee performance as the dependent variable and work motivation as the intervening variable. Data analysis to measure direct effect was carried out using multiple regression analysis, coefficient of determination, F statistical test, and t statistical test. At the same time, the analysis uses path analysis to see the relationship between variables through intervening variables. The results of the partial test analysis showed t-tests 0.518 and 1.938. Meanwhile, the path analysis t-count is 0.058. At the same time, the indirect effect through motivation is 0.262*0.630 = 0.165. The total value of the influence of WFH, directly and indirectly, obtained a total value of 0.223. WFH does not directly affect work motivation and employee performance. While the results of testing the variables through the intervening variable, work motivation, show that there is a significant effect of WFH on employee performance